Flexibility and shape memory of phase change material capable of rapid electric heating function for wearable thermotherapy. (1st December 2022) - Lin, Xuemin; Ling, Ziye; Fang, Xiaoming; Zhang, Zhengguo
Graphical abstract: Highlights: The prepared CPCM exhibits excellent flexibility at room temperature. FCPCM possesses high enthalpy, high thermal conductivity and electrical conductivity. FCPCM has wide temperature range of flexibility and shape memory properties. FCPCM is available for fast heating with low current. For thermal therapy, FCPCM applied to the face and knees, elbows, waist, back, etc. Abstract: Thermotherapy is often preferable to medication and surgery because of its mild side effects and noninvasiveness. However, current research methods are unable to improve the efficiency of pre-treatment resulting in unportable use, and poor room temperature flexibility has become its critical limitation. Herein, a novel conductive flexible composite phase-change material (CPCM) was prepared for high-performance thermotherapy. Styrene ethylene butylene styrene (SEBS) and expanded graphite (EG) absorb paraffin (PA) and silicone oil onto a three-dimensional network. The CPCM possesses a high energy storage density (100.8–164.5 J/g) and sufficient volume conductivity (383.76 S·m −1 ) and can improve the thermal conductivity to 1600 % relative to pure PA. Moreover, it is flexible and possesses shape memory at both room temperature and the phase change temperature (44 ℃). The hardness of the material is 44.5 HA at room temperature and can be reduced to 2.0 HA after phase transition. When heated electrically, it heated threefold faster than when heated by hot air. The material was tested by volunteers and was found to maintain a temperature above 40 °C for more than 30 min. The utilization of this CPCM in thermotherapy is a promising low-cost and environmentally friendly strategy.